Risk Factors for Development of Cytomegalovirus Resistance in Solid Organ Transplantation: A Retrospective Nested Case–Control Study. (4th October 2017) - Sandkovsky, Uriel; Qiu, Fang; Kalil, Andre C; Florescu, Ada; Wilson, Natasha; Manning, Christa; Florescu, Diana F
Abstract: Background: Cytomegalovirus (CMV) infections have a significant impact on morbidity and mortality of solid organ transplant (SOT) recipients. Acquisition of CMV resistance is an emerging problem. Risk factors associated for CMV resistance are not well defined. Methods: We selected SOT recipients who underwent CMV resistance testing between January 2010 and March 2016 and divided them in group 1 Ð cases with genotypic resistance, and group 2 Ð cases with clinical resistance (no genotypic resistance). We selected group 3 of patients with CMV viremia in whom resistance was not suspected. We performed a 1:2:2 matched case–control study (11:22:22 recipients matched by age). We used ANOVA and Kruskal–Wallis for continuous variables, Fisher's or chi-square test for categorical variables and t-test or Mann–Whitney U test to compare groups for continuous variables. Univariate and multiple conditional logistic regression were used to identify risk factors associated with the occurrence of CMV resistance. Results: Patients' demographics are presented in the table. Group 1 compared with group 2 and 3: had higher mean prednisone ( P = 0.01) and tacrolimus levels ( P = 0.03) in the 30 days before resistance testing; did not respond to antiviral therapy ( P < 0.0001); and had higher rate of concomitant fungal infections ( P = 0.03). Group 1 (genotypic resistance) had higher mean CMV DNA viral load at time of resistance testing (log10 4.55 ± 0.88 vs. 4.05 ± 1) compared with group 2 (no resistance), but it did not reach statistical significance ( P = 0.17). CMV resistance was less common in liver and kidney transplant recipients ( P = 0.0007) compared with heart, small bowel and mutivisceral recipients. No difference was seen among groups for duration of antiviral prophylaxis prior to infection, time from transplant to first viremia, rate of viremia while on antiviral prophylaxis, rate of end-organ disease, graft loss and overall survival. Conclusion: Resistant CMV disease is a growing clinical problem. High degree of immunosuppression (reflected by higher rates of concomitant infections, high tacrolimus levels and use of high-dose prednisone) is an important and potentially modifiable risk factor for emergence of CMV resistance, Persistent CMV infection should trigger resistance testing. Disclosures: U. Sandkovsky, Merck: Grant Investigator, Research grant. D. F. Florescu, Merck: Grant Investigator and Scientific Advisor, Research grant and Salary. Shire: Grant Investigator, Research grant and Salary. Chimerix: Grant Investigator and Scientific Advisor, Research grant and Salary. Astellas: Grant Investigator, Research grant. Oxford: Grant Investigator and Scientific Advisor, Research grant and Salary